2020
DOI: 10.1093/jpepsy/jsaa069
|View full text |Cite
|
Sign up to set email alerts
|

Illness Uncertainty Longitudinally Predicts Distress Among Caregivers of Children Born With DSD

Abstract: Objective A subset of parents of children with disorders/differences of sex development (DSD) including ambiguous genitalia experience clinically elevated levels of anxious and depressive symptoms. Research indicates that uncertainty about their child’s DSD is associated with parent psychosocial distress; however, previous studies have been cross-sectional or correlational in nature. The current study is the first to examine the longitudinal trajectory of the relationship between caregiver-pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 43 publications
1
10
0
Order By: Relevance
“…Providers must set an expectation as soon as possible for ongoing, open communication between all parties, especially since parents may experience distress due to the uncertainty associated with DSD and may seek quick fixes (Crissman et al., 2011 ; Roberts et al., 2020 ). Models of shared decision-making as well as related decisional tools have been developed to support ongoing communication between HCPs and families/individuals (Karkazis et al., 2010 ; Sandberg et al., 2019 ; Siminoff & Sandberg, 2015 ; Weidler et al., 2019 ).…”
Section: Chapter 10 Intersexmentioning
confidence: 99%
See 1 more Smart Citation
“…Providers must set an expectation as soon as possible for ongoing, open communication between all parties, especially since parents may experience distress due to the uncertainty associated with DSD and may seek quick fixes (Crissman et al., 2011 ; Roberts et al., 2020 ). Models of shared decision-making as well as related decisional tools have been developed to support ongoing communication between HCPs and families/individuals (Karkazis et al., 2010 ; Sandberg et al., 2019 ; Siminoff & Sandberg, 2015 ; Weidler et al., 2019 ).…”
Section: Chapter 10 Intersexmentioning
confidence: 99%
“…For almost all parents, the birth of a child with intersexuality is entirely unexpected and comes as a shock. Their inability to respond immediately to the ubiquitous question, “Is your baby a boy or a girl?”, their lack of knowledge about the child’s condition, the uncertainty regarding the child’s future, and the pervasive intersex stigma are likely to cause distress, sometimes to the level of PTSD and may lead to prolonged anxiety and depression (Pasterski et al., 2014 ; Roberts et al., 2020 ; Wisniewski & Sandberg, 2015 ). This situation may affect parental care and long-term outcome of their child with intersexuality (Schweizer et al., 2017).…”
Section: Chapter 10 Intersexmentioning
confidence: 99%
“…Data included in the present study are from the time point each caregiver first completed the stigma measures, which varied from baseline to the fourth annual visit. Portions of data from the larger, multisite study have been reported in previous publications with different aims and hypotheses (Perez et al, 2019, 2021; Roberts, 2020; Sharkey et al, 2018; Suorsa et al, 2015).…”
Section: Methodsmentioning
confidence: 99%
“…Far fewer parents showed chronic or elevating distress in that year, whilst mothers reported more distress than fathers overall [17]. The same research collaboration found that levels of illness uncertainty predicted parents' depression and anxiety in the year after infant surgery [18]. Medical interventions may cause distress because parents lack sufficient time to process difficult emotions, and VSC that pose no health risk can be framed as disordered in healthcare settings [19].…”
Section: Parental Distressmentioning
confidence: 98%